Controlled sliding as injury prevention - Kersting, U. G.; Lysdal, F. G. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
In this chapter, the background and possible mechanisms of lateral ankle injuries are presented. As these injuries are among the most common sports injuries, especially in indoor sports, and have often been trivialized, the focus of research on these injuries has increased significantly. In particular, a larger number of acute injuries have recently been quantitatively analyzed, which has led to a changed representation of the injury mechanism. Based on this, an innovative prophylactic intervention is presented, which was also tested in a follow-up study. The results show that the idea behind this intervention, which takes the updated injury mechanism into account, leads to a reduction in injuries as well as an attenuation of the concomitant injury-related symptoms.